Self-evaulation of personal physical health, accidents while performing duty and preventive treatment of stress in Prison Service - Andrzej Piotrowski (Nofer Institute of Occupational Medicine, 2018)
Background The purpose of the work was to assess the level of health, estimate the number of accidents during service and to identify the use and perceived effectiveness of the prevention of occupational stress in Prison Service (PS). Material and Methods The questionnaire survey was carried out in 2015 at the Central Prison Service Training Center in Kalisz and in selected prisons and detention centers for the group of 250 officers. The questionnaire, which had been constructed for the purpose of the cooperation with the Occupational Safety Body of the Central Board of the Prison Service, was used. There were questions about the frequency of headaches, hypertension, sleep disorders, taking painkillers, accidents during service and prevention of occupational stress. Results For frequent headaches, sleep disorders and hypertension complain 9-14% of officers. Every 8th officer in the period of 5 years preceding the survey had an accident during his service. Participation rate in the stress prevention and interpersonal training workshops accounted for 70%, and most officers consider them to be effective. The lack of the possibility to make holidays in accordance with the schedule represents the percentage share of 10% of the sample tested, and every 20th of the PS must stop it due to the situation in the service. It was revealed that preferences in the area of applied coping strategies turned out to be slightly differentiating between officers undertaking and not undertaking activity in the field of occupational stress prevention. Conclusions Officers serving in the multi-shift system and with a longer service period should be covered by greater prevention from the PS work medicine. Conducting training in the prevention of occupational stress should take place at the beginning of the service. Med Pr 2018;69(4):425-438